Original paperThe pilot study assessing efficacy and versatility of novel therapy for neoplastic ulceration: clinical and microbiological aspects - Sopata, Maciej; Tomaszewska, Elżbieta; Muszyński, Zygmunt; Ciupińska, Maria; Kotlińska-Lemieszek, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Neoplastic ulcers are chronic and, most often, irreversible lesions caused by proliferation of tumor cells infiltrating and damaging skin tissues. The treatment of neoplastic ulcers is a very difficult and time-consuming process. So, is very important to find methods of controlling this type of chronic wounds. Aim : To evaluate the efficiency of monitored treatment of neoplastic ulcers by means of providing moist wound environment dressings and antiseptic to the group of patients with an advanced stage of tumor, with particular focus on the impact of the treatment applied on the clinical condition of the ulcers; to evaluate the impact of the treatment applied on the dynamics of bacterial flora in neoplastic ulcers, with particular focus on the presence of alarm pathogens; to conduct a risk analysis of the occurrence of local and systemic complications during treatment. Material and methods : This was a prospective pilot clinical study of 30 patients with malignant ulcers, 13 male and 17 female aged from 24 to 92 years treated with octenidine antiseptic and dressing set for 3 weeks. The wounds were clinically assessed for the changes of amount of necrotic tissue, exudate level and type, malodour and pain level during treatment. At the baseline and after 3 weeks of treatment, the wounds were swabbed for microbiological assessment. Results: The used scheme of treatment is efficient and brings clinical improvement in all treated ulcers. During the 3-week treatment, reduction of necrotic tissue, decrease in the level of exudate, pain and malodour was observed in all patients (p < 0.05). High activity of octenidine against Gram(–) and Gram(+) bacteria was observed. The use of octenidine dihydrochloride correlated with a progressing eradication of multiresistant strains and alarm pathogens (p < 0.001). No serious adverse effects or significant symptoms of intolerance of the applied treatment were observed.